ENHANCING EFL SPEAKING SKILLS THROUGH SPOTIFY: THE POWER OF INTERACTIVE COMMENTS - Lubis, Devi Nauli; Wahono, Suparwoto Sapto (English Review: Journal of English Education, 2024)
The ability to communicate verbally is essential for learners to interact within society, particularly in mastering English speaking skills. However, many students struggle with speaking due to a lack of understanding, confidence, and fear of criticism. This study aims to motivate students to enhance their speaking skills through the use of the Spotify application for commenting. Utilizing a qualitative descriptive approach, data were collected through observations, interviews, and document analysis involving 20 students. The findings indicate that the use of Spotify significantly motivated students and improved their speaking abilities. This is evidenced by the variety and quality of comments submitted by the students. The results suggest that integrating digital media like Spotify in language learning can effectively enhance students' speaking skills by providing a flexible and engaging platform for practice.